2006
DOI: 10.1063/1.2363816
|View full text |Cite
|
Sign up to set email alerts
|

Electrical current-induced structural changes and chemical functionalization of carbon nanotubes

Abstract: We demonstrate that high current densities, combined with air exposure can slice, weld, and chemically functionalize multiwalled carbon nanotubes (CNTs) with carboxyl and allyl moieties, and alter the electrical properties. The conductance of thin film assemblies of CNTs increases by 150%, indicating that the increase in the number of low-resistance pathways caused by CNT junction formation offsets the conductance decrease expected from defect creation, surface functionalization, and fissure. Such welded high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
(18 reference statements)
1
8
1
Order By: Relevance
“…In a similar approach, Ramanath and co-workers extended the functionalization of CNTs by focused-ion-beam irradiation. The authors showed that nanoparticles, fluorescent microspheres, an amino acid, or a metalloprotein could be assembled on CNT surface without aggressive wet chemical oxidation.…”
Section: Covalent Approachesmentioning
confidence: 99%
“…In a similar approach, Ramanath and co-workers extended the functionalization of CNTs by focused-ion-beam irradiation. The authors showed that nanoparticles, fluorescent microspheres, an amino acid, or a metalloprotein could be assembled on CNT surface without aggressive wet chemical oxidation.…”
Section: Covalent Approachesmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) , have attracted interest because of their small diameter, large surface-to-volume ratio, great structural integrity, high electrical and thermal conductivity, good thermal and chemical stability, and exceptional strength and resilience. Functionalization of CNTs with various chemical groups , and nanocrystals can further enhance the properties of CNTs, and CNTs have been considered as superior supports for nanocrystal catalysts. , In fact, hybrid materials consisting of nanocrystals distributed on the surfaces of CNTs could potentially display not only the unique properties of nanocrystals , and those of nanotubes but also additional novel properties. Recently, such CNTs with nanocrystals have been shown to be promising for various energy applications including solar cells, , fuel cells, , Li−ion batteries, and hydrogen storage. , …”
Section: Introductionmentioning
confidence: 99%
“…In general these strategies can be divided into two groups: a pre-deposition functionalization (functionalization of the SWCNT material before the network is made) and a post-deposition functionalization. The latter case again can be divided by different approaches which are: a) direct cross-shell linking between individual CNTs by irradiation with electrons [19] or UV light, [20] and by current induced structural changes [21] or b) various ways of chemical functionalization, such as adsorbing individual molecules with functional groups, [22][23][24] coating with polymers containing functional groups [5,[25][26][27] and covalent bonding of functional groups. [28] In all cases, the functional groups act as electron donors/acceptors and the increased conductivity can be explained in terms of doping of semiconducting SWCNTs, which are the majority in bulk SWCNT samples.…”
mentioning
confidence: 99%